A comparative study on the thermo-oxidative stability of polyethylene - Real, L. P. (2012)
The main goal of this work is to establish a correlation between the oxidation induction time (OIT) and the oxidation induction temperature (OIT*), which are frequently used to assess the thermo-oxidative stability of polyolefins, either as raw-materials or as finished products. Several tests have been performed at different temperatures (200, 210 and 220 C) using a set of polyethylene (PE) samples from different sources. The correlations found - based on a quadratic regression – make it possible to estimate the OIT value based on experimental data of OIT* and vice-versa. This method can be quite useful in cases when the PE is highly stabilized so that the OIT test at 200 C is expected to last for hours. Additionally, an Arrhenius plot has been developed to obtain the activation energy (Ea) associated with the beginning of the thermo-oxidation for each PE, which also allows us to determine OIT from calculated Ea. All estimated values, obtained by the developed regression models, using unknown specimens, have been confirmed by experimental testing. The regression models have also been checked by a residual analysis as a way to evaluate their reliability. The contribution of the uncertainties of measurement and calculation has also been evaluated, leading to increased reliability of the findings.